2012
DOI: 10.1148/radiol.11103506
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Needle-Out Patient-Rollover Time after Percutaneous CT-guided Transthoracic Biopsy of Lung Nodules: Effect on Pneumothorax Rate

Abstract: Rapid needle-out patient-rollover time during percutaneous CT-guided transthoracic lung biopsy reduces the rate of overall pneumothorax and pneumothorax necessitating a drainage catheter. Use of this technique attenuates the influence of traditional risk factors for pneumothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 17 publications
3
48
0
1
Order By: Relevance
“…Emphysema is one of the inevitable established significant risk factors of pneumothorax in various studies [1][2][3][4][5], and the current results were in accordance to this observation in both study groups.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Emphysema is one of the inevitable established significant risk factors of pneumothorax in various studies [1][2][3][4][5], and the current results were in accordance to this observation in both study groups.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies [5][6][7][8][9][10][11][14][15][16][17] reported that the longer is the needle path from the pleural surface to the lesion, the greater is the incidence of pneumothorax. Traversing interlobar fissures by the biopsy needle was another significant risk factor of pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations